Unveiling the Economic Significance and Socioeconomic Implications: A Comprehensive Analysis of the Role of Leather Industries in the Development of the Indian Economy - Yadav, Brijesh singh (Journal of Advanced Research in Glass, Leather and Plastic Technology; Vol 6 No 1 (2023): Journal of Advanced Research in Glass, Leather and Plastic Technology, 2023)
One of the oldest traditional industries is the leather industry. In the manufacturing of leather and related products, it significantly contributes to economic growth, balanced regional development, job creation, and overall poverty reduction. Given that India is home to 21% of the world's cattle and buffalo population as well as 11% of the world's goat and sheep, the leather industry is blessed with an abundance of raw materials.Strengths including a trained workforce, cutting-edge technology, increased industry adherence to global environmental standards, and the steadfast backing of related industries are added to this. An estimated 2.5 million individuals, largely from the weaker sections of society, have jobs thanks to the leather industry, which is a sector that generates a lot of employment. In the leather products business, women make up around 30% of the workforce.